Effect of Climate Change on Crop Yield in Nigeria - Olumide, Ayodele (International Journal of Agriculture, 2024)
Purpose: The aim of the study was to analyze the effect of climate change on crop yield in Nigeria. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Climate change in Nigeria has caused declining crop yields due to rising temperatures, changing rainfall patterns, and increased frequency of extreme weather events like droughts and floods. This trend adversely affects staple crops like maize and rice, despite adaptation efforts through resilient crop varieties and better agricultural practices. Unique Contribution to Theory, Practice and Policy: Environmental determinism, vulnerability theory & resilience theory may be used to anchor future studies on effect of climate change on crop yield in Nigeria. Encourage the adoption of climate-smart agricultural practices, such as conservation agriculture, agroforestry, and integrated crop-livestock systems, that enhance resilience to climate change while improving productivity and sustainability. Develop policies that support the adoption of climate-resilient agricultural practices, incentivize the use of climate-smart technologies, and facilitate access to climate information and advisory services for farmers.